Meteorological Register and Readability in BMKG Press Releases During the Sumatra Floods in Late 2025: Pedagogical Implications for Literacy - Dimas Adika; Anita Rusjayanti; Noprival; Aal Inderajati; Henry Trias Puguh Jatmiko (UIN Raden Mas Said Surakarta, 2026)
The essential role of risk communication in the disaster involved in the extreme flood crisis on Sumatra in the end of 2025 was critical to human safety. Nonetheless, the press releases of Meteorology, Climatology, and Geophysics Agency (BMKG) sometimes had complicated language, and this was might unable to attract the masses to identify with this natural phenomenon. This study explored the meteorological registers and readability of BMKG press releases and how its impact on pedagogy. This study employed the Mixed Methods Research (MMR) approach by analyzing official press releases of Aceh, North Sumatra, and West Sumatra BMKG on November to December 2025 flood crisis. The Flesch Reading Ease (FRE) formula was used to measure the quantitative readability, and the qualitative analysis was used to examine the differences between the main texts and the appendices. The results indicate that there is a shift in language use: the Main Texts are characterized by a scientific register, high lexical density, global meteorological vocabulary (e.g., MJO, IOD, TC), and unclear acronyms, indicating characteristic of the scientific language prevails. Contrastingly, the Appendices are written with a practical register, which provides easy to follow clear actionable instructions. This finding is supported by FRE scores, showing that the Main Texts score is between -43.75 and 17.8 (on a scale of 0-100, where lower scores indicate higher complexity), whereas the Appendices score is far better, between -34,14 and 40,29. This significant gap between language and text function makes the reasoning behind meteorological warnings might inaccessible to the people, causing them to obey without being able to fully comprehend the underlying meteorological risks and the necessity of the warnings. Then, this study proposed four stages of teaching model as pedagogy impact as follow: analysis, deconstruction, reconstruction and evaluation, to prepare future science communicators to bridge the gap between expert information with public understanding.